Rattan litter-collecting structures attract nest-building and defending ants. (3rd August 2019) - Liu, Kunpeng; Mansor, Asyraf; Ruppert, Nadine; Lee, Chow Yang; Azman, Nur Munira; Fadzly, Nik
ABSTRACT: Rattan is an important climbing palm taxon in Malaysian tropical rain forests. Many rattan species have unique structures directly associated with certain ant species. In this study, four rattan species ( Daemonorops lewisiana, Calamus castaneus, Daemonorops geniculata and Korthalsia scortechinii ) were inspected and documented in a field survey concerning their relationships with several ant species. We noticed that two rattan species ( D. lewisiana and C. castaneus ) were more likely to be associated with ants compared to their neighbouring rattan ( Plectomia griffithii ). However, D. lewisiana and C. castaneus did not directly provide shelters for ant colonies, but possessed unique structures: upward-pointing spines and funnel-shaped leaves, which are equipped to collect more litter than P. griffithii . To test our litter collecting hypothesis, we measured the inclination of spines from the stem. Our results showed the presence of ant colonies in the litter-collecting rattans ( D. lewisiana and C. castaneus ), which was significantly higher compared to a non-litter-collecting rattan ( P. griffithii ). We propose a complex and novel type of adaptation (litter-collection and provision of nesting materials) for rattans, which promotes interactions between the rattan and ants through the arrangements of leaves, leaflets, and spines. In return, the rattan may benefit from ants' services, such as protection, nutrient enhancement, and pollination.